2021
DOI: 10.1038/s41523-021-00343-4
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of HER2-low expression from primary to recurrent breast cancer

Abstract: About a half of HER2-negative breast cancer (BC) show HER2-low expression that can be targeted by new antibody-drug conjugates. The main aim of this study is to describe the evolution of HER2 expression from primary BC to relapse by including HER2-low category in both primary and recurrent BC samples. Patients with matched primary and relapse BC samples were included. HER2 was evaluated according to ASCO/CAP recommendations in place at the time of diagnosis. A cutoff of >10% cells staining for HER2-positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 41 publications
13
111
2
Order By: Relevance
“…In terms of HR status, a significant difference was observed between the two groups since HER2-low breast cancer was enriched with HR+ tumors, while the HER2-zero cohort was enriched with HR-cases. Such correlation between HR signaling and HER2-low expression has also been reported in a retrospective, large-cohort, gene expression profiling study, where PAM50-based-subtypes accounted for approximately 80% of HER2-low-positive cases (Miglietta et al, 2021).…”
Section: Insights From the Biological Landscape Of Her2 Low Expressionsupporting
confidence: 70%
See 2 more Smart Citations
“…In terms of HR status, a significant difference was observed between the two groups since HER2-low breast cancer was enriched with HR+ tumors, while the HER2-zero cohort was enriched with HR-cases. Such correlation between HR signaling and HER2-low expression has also been reported in a retrospective, large-cohort, gene expression profiling study, where PAM50-based-subtypes accounted for approximately 80% of HER2-low-positive cases (Miglietta et al, 2021).…”
Section: Insights From the Biological Landscape Of Her2 Low Expressionsupporting
confidence: 70%
“…In terms of HR status, a significant difference was observed between the two groups since HER2-low breast cancer was enriched with HR+ tumors, while the HER2-zero cohort was enriched with HR- cases. Such correlation between HR signaling and HER2-low expression has also been reported in a retrospective, large-cohort, gene expression profiling study, where PAM50-based-subtypes accounted for approximately 80% of HER2-low-positive cases ( Miglietta et al, 2021 ). Concerning the pathological complete response (pCR) data, in the HR+ cohort, the authors observed a lower pCR in patients with HER2-low breast cancer compared to those with HER2-zero disease with no effect on long-term survival ( Denkert et al, 2021 ).…”
Section: Rebooting Her2 Testing In Breast Cancersupporting
confidence: 65%
See 1 more Smart Citation
“…While more studies are required, this finding has important implications for future diagnostic algorithms given the inherent challenge for pathologists to distinguish HER2-zero and HER2-low tumours by IHC in clinical practice. It also warrants further study for a general understanding of HER2-low disease biology given that HER2 status can drift with treatment [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although glandular autograft is known to be the most effective technique, in place of alternative therapies, autologous transplantation is not always possible. Allografts are a good way to treat patients who are unable to receive autograft treatment, but this has limited success due to the side effects associated with tissue rejection [ 4 ]; therefore, MSC therapy as a treatment for hypoparathyroidism is expected to be used clinically in the future.…”
Section: Introductionmentioning
confidence: 99%